Experimentally Comparative Study on Different Strengthening Methods of Reinforced Concrete Deep Beams - Osama Megahed El Battawy; Khaled Farouk El Kashif; Hany Ahmed Abdalla (Civil Engineering Journal, 2019)
The aim of this study is to investigate the effect of strengthening reinforced concrete deep beams. An experimental study was done using six reinforced concrete deep beams have the same dimensions of 1150×800×150 mm, and subjected to mid-span concentrated load up to failure. Beams were different in the type, Location of strengthening and the ratio of reinforcement. Beams were divided into three groups. The first group included beams strengthened internally by single strut and either vertical or horizontal additional reinforcement. The second group included beams strengthened using double embedded strut or using CFRP as external strengthening. The third group included one beam strengthened using inclined stirrups. One of the specimens was tested without any strengthening and one specimen was strengthened by external CFRP sheets for comparison purposes the results of the experimental study shown remarkable improvement for using each type of strengthening. Results shown that using the mechanism of increasing stirrups by double rate and using single strut reinforcing is the optimum choice. This is due to the fact that this type of strengthening provides significant increase in the beam capacity in additional to the enhanced behavior of the beam. By this study comparison between each type of strengthening was done and the optimum type to be used in accordance with parameters of gained load capacity of tested deep beams.